An assessment of the use of gender mainstreaming to promote equality in pre and post 2011 revolutionary Egypt - Shash, Farah (AUC Knowledge Fountain, 2012)
Although the Egyptian constitution states that all Egyptians are equal before the law and equal in rights and duties, many gender inequalities existed before and continue to exist after the Egyptian 2011 revolution. One approach to creating gender equality is Gender Mainstreaming. This approach aims to achieve gender equality through governments and institutions, asking them to assess the implications and consider the needs and experiences of both men and women in any planned action, legislation, policy or program. This study examines how Gender Mainstreaming has been implemented in Egypt, the challenges it has faced, the opportunities available for further implementation, and its potential for achieving the goal of gender equality in the face of the political and social changes taking place in post- revolutionary Egypt. Qualitative semi-structured interviews were conducted with gender consultants and gender focal points in international and national non-governmental organizations, human rights and feminist organizations, and governmental institutions. The research questions addressed in this study were: 1) How has Gender Mainstreaming been implemented before and after the revolution? 2) Has Gender Mainstreaming been effective at promoting gender equality? 3) What are the challenges and opportunities of Gender Mainstreaming as it has been implemented in Egypt? And 4) what is the potential for implementing Gender Mainstreaming in post-revolutionary Egypt? The results of this research show that Gender Mainstreaming has potential and needs to be implemented in post-revolutionary Egypt, especially with the rise of conservatism and the changes occurring in the political and social systems, so that gender issues and womenâ s needs will not be ignored. However, Gender Mainstreaming will not be effective unless the appropriate environment and prerequisites are in place. These prerequisites are 1) having the political will for implementation, 2) accountability, 3) involvement of men in the process, 4) reaching consensus with stakeholders about the definition of gender equality, 5) applying a culturally sensitive model, and 6) using other approaches that also aim at empowering women and ask for womenâ s rights.